Geopolitical Impact on Transformation of Territorial Organization of Russian Pipeline Transport in the Post-Soviet Time - Pototskaya, Tatyana I.; Katrovskiy, Alexander P.; Chasovskiy, Vladimir I. (International Journal of Energy Economics and Policy, 2016)
The article presents the research on transformation of territorial organization of Russian pipeline transport in the post-Soviet time, considering its relations with neighboring countries. The research identifies general ways of such transformation: the influence of Russia’s desire to escape from the dictate of the transit countries exporting energy; the impact of Russia’s struggle for the transportation of gas and oil extracted in the Caspian Sea basin; the influence of the struggle for the transportation of oil and gas in the Asia-Pacific region. A new database including the main pipelines and sea ports in Russia, revealed correlations in the development of pipeline transport in the post-Soviet period with the development of infrastructure of the country’s sea transport. The article identifies positive changes in the transport infrastructure (construction of Russian alternative pipeline projects), which will reduce the degree of Russian dependence on relations with neighboring countries, as well as negative changes (construction of alternative Russian pipeline projects). The attention is focused on changing geopolitical importance of neighboring to Russia states (Turkey, Kazakhstan and China) under the influence of transformation of the country pipeline transport. Keywords: geopolitics; Russia’s geopolitical position; Russian pipeline transport; post-Soviet space JEL Classifications: L9, L95